SOMALI ARABIC POETS - SELECTED CASE STUDIES (1981)
This study contains representative selection of Somali Arabic poetry, which gives a clear idea of the quantity and quality of Somali Arabic poetry as well as its literary standard, its themes, its contents and its forms. Entitled "Somali Arabic Poets - Selected Case Studies", it comprises two parts: "Background Survey" and "Selected Somali Arabic Poets". "Part One" contains three Sections, the first of which is devoted to a brief study of Somalia - geographically, historically and politically. The second is devoted to a study of the place and importance of Somali poetry (in Somali language) in the Somali Culture, and the last is devoted to a study of the emergence and development of Arabic and its literature in the Somali Peninsula. "Part Two" also contains three section s, The first of these is devoted to a study of the life and works of the eminent poet, “zaylaci”, the second is devoted to a study of the life and literary production of the prolific poet, "Hajj Sufi", and the last is devoted to a study of the life, scholarship and Arabic works of the remarkable leader and the famous bilingual poet "the Sayyid". This study ends with concluding remarks, which sum up the findings of this research.